Racjonalizacja religii a dominacja społeczna (3). Od Woltera i wolterianizmu do rozdziału Kościoła od państwa - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2011)
Zbigniew Drozdowicz – RATIONALIZATION OF RELIGION AD SOCIAL DOMINATION. FROM VOLTAIRE AND VOLTAIRIANISM TO THE DIVISION OF STATE AND CHURCH Recalling such a phenomenon in the Western culture as voltairianism puts a big question mark over the weberian evaluation of participation in social changes in modern and contemporary Europe of intellectuals of Enlightment. In fact at the beginning they were perceived as big mouths and they did use strong language in the criticism of Christianity and those, who did welcome it with under-standing were very few. They did went from those words to actions very quickly, which meant pushing Christianity on the margins of social life. The ending of those actions in such countries like France or Italy was the introducing of the formal and legal division of state and Church, as well recognition by the influential social circles of the thesis, that religion and religiosity is a private matter of man and citizen. Those deep changes in thinking on religion had been caused by the spirit of Voltaire, although not always expressed with such a strong language like the one used by Voltaire himself, but always critical towards in the involvement of the Catholic Church in matter of public life.